2011
DOI: 10.1039/c1cp22158b
|View full text |Cite
|
Sign up to set email alerts
|

ACMA (9-amino-6-chloro-2-methoxy acridine) forms three complexes in the presence of DNA

Abstract: The interaction of ACMA (9-amino-6-chloro-2-methoxy acridine) (D) with DNA (P) has been studied by absorbance, fluorescence, circular dichroism, spectrophotometry, viscometry and unwinding electrophoresis. A T-jump kinetic study has also been undertaken. The experimental data show that, totally unlike other drugs, ACMA is able to form with DNA three complexes (PD(I), PD(II), PD(III)) that differ from each other by the characteristics and extent of the binding process. The main features of PD(I) fulfil the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Analysis of DNA binding of the compound 9-amino-6-chloro-2-methoxyacridine (ACMA) showed that fluorescence quenching of ACMA by DNA is informative of intercalation, whereas the absorption spectrum may shed light into possible external binding. It was suggested that the DNA-ACMA interaction is not a simple one and that both the intercalative as external binding can be present [26]. In this way, the kind of interaction of the acridine derivatives produced is consistent both with intercalation as external binding.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Analysis of DNA binding of the compound 9-amino-6-chloro-2-methoxyacridine (ACMA) showed that fluorescence quenching of ACMA by DNA is informative of intercalation, whereas the absorption spectrum may shed light into possible external binding. It was suggested that the DNA-ACMA interaction is not a simple one and that both the intercalative as external binding can be present [26]. In this way, the kind of interaction of the acridine derivatives produced is consistent both with intercalation as external binding.…”
Section: Resultsmentioning
confidence: 82%
“…Distinct spectroscopic behaviors stems from the different nature of the substituents located around the main acridine structure that can affect the kinetic and thermodynamic aspects of DNA binding [26]. Absence or presence of an amino moiety at position 3 of the thiazolidin-4-one ring can explain the hypochromic or hyperchromic effect presented by compounds 4 and 5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This feature is often related to unwinding of the double helix, quite a common effect in intercalation. 16 A new, positive, induced CD band appeared at 345 nm, characteristic of the [2c′] + /DNA complex formation, since neither DNA nor [2c′] + displayed any CD signal in that region. The dependence of the molar ellipticity at 275 nm on the C D /C P ratio reveals that the binding isotherm bears out the formation of PD II .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[8][9][10] The behaviour of ACMA toward DNA contrasts with that of the acridine proflavine, whose stacking with the DNA bases results in fluorescence enhancement. 11 ACMA has been shown recently to form three different complex species with Calf Thymus (CT)-DNA, 12 which differ from each other by the mode and extent of interaction. CT-DNA is extremely heterogenic both compositionally and structurally; hence, in principle it should not be discarded that the different modes of binding bear relation with the different structural or compositional domains (e.g., ATrich vs. GC-rich), which may display different affinity with the drug.…”
Section: Introductionmentioning
confidence: 99%